TECTONOPHYSICAL ZONING OF ACTIVE FAULTS OF THE BAIKAL RIFT SYSTEM - Yu. L. Rebetsky; A. A. Dobrynina; V. A. Sankov (Геодинамика и тектонофизика, 2024)
Tectonophysical zoning of active faults of the Baikal rift system (BRS) was performed based on the degree of hazard caused by the generation of earthquakes of magnitude 7.0 and higher. The first basis for this procedure was the results of the natural stress state reconstruction, earlier performed from seismological indicators of rupture deformations (earthquake focal mechanisms). The second important element of fault zoning was electronic maps of active faults of Eurasia hosted on the GIN RAS sever. Within the algorithmic framework for Rebetsky’s method of cataclastic analysis, both of these datasets allowed calculating the Coulomb stresses for the segments of the BRS faults. During the study, a development of the cataclastic method has been carried out in using a diagram of brittle fracture as the Mohr–Coulomb model, considering a decrease in the range of positive Coulomb stress values with an increase in effective normal stress levels. Such an approach provides a more reliable identification of the fault segments with the maximum Coulomb stress levels. The performed calculations showed that in the BRS crust there are several up to 50 km long fault segments having critically high (80–100 % of the maximum) and high (40–80 % of the maximum) Coulomb stress levels. It is these corebased hazardous zones that are considered as places where seismogenic ruptures of future М>7.0 earthquakes may start. There have been distinguished three zones that present such hazard: 1) in the western segment of the BRS in the western part of the Tunka Valley in the Tunka, Khamardaban-Mondy and Baikal-Mondy fault systems; 2) in the Selenga River delta in the Proval, Delta, Ust-Selenga and Sakhalin-Enkhauk fault systems; 3) within the northeastern flank of the BRS on the fault system of the Muyakan basin (along the North Muya ridge). It is proposed to perform tectonophysical monitoring of changes in the stress state of these three zones and make observations of their surface motions using remote sensing methods.